2013
DOI: 10.3748/wjg.v19.i14.2171
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of human epidermal growth factor receptor 2 expression with clinicopathological characteristics and prognosis in gastric cancer

Abstract: Patients with intestinal type gastric cancer (GC), well-differentiated GC and poorly-differentiated GC without lymph node metastasis, may all represent suitable candidates for targeted therapy using Herceptin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
58
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 36 publications
12
58
4
Order By: Relevance
“…SUV max was significantly lower in the HER2-positive group than in the HER2-negative group. Our data also demonstrated that HER2 expression is more common in well-or moderately differentiated adenocarcinoma than in poorly differentiated adenocarcinoma; this finding is consistent with the findings of previous studies (20)(21)(22). In addition, well-or moderately differentiated adenocarcinoma had significantly lower 18 F-FDG uptake than did poorly differentiated adenocarcinoma, partly explaining why patients with HER2 expression had a low SUV max (excluding signet-ring cell carcinoma from the analysis).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…SUV max was significantly lower in the HER2-positive group than in the HER2-negative group. Our data also demonstrated that HER2 expression is more common in well-or moderately differentiated adenocarcinoma than in poorly differentiated adenocarcinoma; this finding is consistent with the findings of previous studies (20)(21)(22). In addition, well-or moderately differentiated adenocarcinoma had significantly lower 18 F-FDG uptake than did poorly differentiated adenocarcinoma, partly explaining why patients with HER2 expression had a low SUV max (excluding signet-ring cell carcinoma from the analysis).…”
Section: Discussionsupporting
confidence: 82%
“…The role of HER2 as a prognostic factor in gastric carcinoma has been controversial. Some studies failed to find an association with prognosis (21,25), whereas others found a direct correlation between HER2 expression or amplification and poor survival (22,26). In our study, most cases were from recent years and the sample size was small.…”
Section: Discussionmentioning
confidence: 76%
“…Regarding anatomical location similar finding have been reported, with no difference between proximal and distal tumor, as we have found in our study (3,9,10,14,18,21) . Most studies conducted in Asia have also reported reactivity rates of 11.7% to 15.74%, similar to our findings, as well as the predominance of HER2 expression in the intestinal subtype (11,16,17,22) . Only one study from Japan showed different prevalence of HER2 expression regarding to anatomical distribution.…”
Section: Discussionsupporting
confidence: 80%
“…Hoffmann's criteria is based on the percentage of cells with membrane-like staining (11,12) . Grades are classified as follows: grade 0: no reaction or <10% reactivity in tumor cells; grade 1+: weak reactivity >10% of the tumor cells; with reactivity only in part of the membrane; grade 2+: moderate reactivity in >10% of the cells, with staining across the lateral and basolateral membrane: grade 3+: strong reactivity with intense staining of the lateral and basolateral membrane in >10% of the cells.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding HER2 and EGFR, our results were similar to those of previous reports with regard to the clinicopathological features and prognosis of each RTK-overexpressing tumor [26,[36][37][38][39][40][41]. However, contrary to previous reports, MET-overexpressing GACs tended to be associated with a rather favorable outcome in our study [25,42,43].…”
Section: Discussioncontrasting
confidence: 57%